Associations of circulating choline and its related metabolites with cardiometabolic biomarkers: an international pooled analysis. Issue 3 (21st May 2021) - Pan, Xiong-Fei; Yang, Jae Jeong; Shu, Xiao-Ou; Moore, Steven C; Palmer, Nicholette D; Guasch-Ferré, Marta; Herrington, David M; Harada, Sei; Eliassen, Heather; Wang, Thomas J; Gerszten, Robert E; Albanes, Demetrius; et al.
ABSTRACT: Background: Choline is an essential nutrient; however, the associations of choline and its related metabolites with cardiometabolic risk remain unclear. Objective: We examined the associations of circulating choline, betaine, carnitine, and dimethylglycine (DMG) with cardiometabolic biomarkers and their potential dietary and nondietary determinants. Methods: The cross-sectional analyses included 32, 853 participants from 17 studies, who were free of cancer, cardiovascular diseases, chronic kidney diseases, and inflammatory bowel disease. In each study, metabolites and biomarkers were log-transformed and standardized by means and SDs, and linear regression coefficients (β) and 95% CIs were estimated with adjustments for potential confounders. Study-specific results were combined by random-effects meta-analyses. A false discovery rate <0.05 was considered significant. Results: We observed moderate positive associations of circulating choline, carnitine, and DMG with creatinine [β (95% CI): 0.136 (0.084, 0.188), 0.106 (0.045, 0.168), and 0.128 (0.087, 0.169), respectively, for each SD increase in biomarkers on the log scale], carnitine with triglycerides (β = 0.076; 95% CI: 0.042, 0.109), homocysteine (β = 0.064; 95% CI: 0.033, 0.095), and LDL cholesterol (β = 0.055; 95% CI: 0.013, 0.096), DMG with homocysteine (β = 0.068; 95% CI: 0.023, 0.114), insulin (β = 0.068; 95% CI: 0.043, 0.093), and IL-6 (β = 0.060; 95% CI: 0.027, 0.094), but moderate inverse associations of betaine with triglycerides (β = −0.146; 95% CI: −0.188, −0.104), insulin (β = −0.106; 95% CI: −0.130, −0.082), homocysteine (β = −0.097; 95% CI: −0.149, −0.045), and total cholesterol (β = −0.074; 95% CI: −0.102, −0.047). In the whole pooled population, no dietary factor was associated with circulating choline; red meat intake was associated with circulating carnitine [β = 0.092 (0.042, 0.142) for a 1 serving/d increase], whereas plant protein was associated with circulating betaine [β = 0.249 (0.110, 0.388) for a 5% energy increase]. Demographics, lifestyle, and metabolic disease history showed differential associations with these metabolites. Conclusions: Circulating choline, carnitine, and DMG were associated with unfavorable cardiometabolic risk profiles, whereas circulating betaine was associated with a favorable cardiometabolic risk profile. Future prospective studies are needed to examine the associations of these metabolites with incident cardiovascular events.